Instability of National Agricultural Research Systems in Sub-Saharan Africa: Lessons from Nigeria - Idachaba, F. S. (International Service for National Agricultural Research, 1998)
NARS leaders and managers are concerned not just about an adequate level of resources, but also the stability of resources and institutional sustainability. Here, we examine six types of instability (policy, program, institutional, funding, research staff, and governance instability) using estimated instability indices to give empirical results on the levels of instability in Nigeria's research institutes. Among other results, the findings confirm the proposition that capital budgets tend to be more unstable than recurrent budgets. The report presents empirical indicators and analyses at the institute-specific level that NARS leaders and managers can use in their discussions with decision makers and in regional and global policy dialogues. The constraints on research institutes that induce instability are examined within the framework of a hierarchy of constraints. The implications of the analysis are examined and strategies for strengthening the stability of the Nigerian NARS are suggested.